SENSORS AND DEVICES FOR RECEIVING HUMAN BIOSIGNALS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article it is discribed some known methods and devices for detecting and taking biosignals (sphygmosignals) at the radial artery which result from heartbeat. And also suggested some new methods and devices using a strain gauge, Hall magnetic sensor, laser distance measurer.